A Compact Wideband Flexible Circularly Polarized Implantable Antenna for Biotelemetry Applications - Ahmad, S; Khabba, A; Ghaffar, A; Li, XJ (IEEE, 2021)
Flexible implantable antennas have got much attention in the field of biotelemetry applications. So, a circularly polarized compact size wideband implantable antenna for the applications of biomedical telemetry is presented in this research work. The proposed design is being operated in ISM (industrial scientific, and medical) band at 5.8 GHz for medical applications. The antenna consists of the discrete ground circular patch and a CPW (coplanar waveguide) fed radiating patch printed on a Polyimide substrate. The overall size of the design is 5×3×0.15mm3 . The antenna covers the bandwidth from 3.4 GHz to 7 GHz (3.6 GHz). The design is being simulated inside human tissues like skin, fat, and muscle. The antenna gives circularly polarized behaviour at 5.8 GHz. This proposed design is well-suited for medical implantable applications.
Keywords: Biomedical telemetry; Meetings; Polyimides; Muscles; Skin; Coplanar waveguides; Fats